Megatrends 2000: Ten New Directions for the 1990's - John Naisbitt and others; NAISBITT (John); ABURDENE (Patricia) (New York Avon Books, 1990)
An invaluable guide to a rapidly changing world Nearly two decades have passed since thepublication of the groundbreaking national bestsellerMegatrends--and a remarkable number of itscontroversial prophecies have come to pass. Nowthe forecasters who accurately predicted the shape ofthe '80s turn their sights on the coming new century.And what they see will astound, excite, and profoundlytouch the lives of each and every one of us.
Keywords: Social indicators--United States; Social prediction--United States; United States--Social conditions--1980; United States--Economic conditions--1981-2001